The Influence of Nutritional Factors on the Quality of Life of Cancer Patients: A Scooping Review - Dhanang Efendi; Zulfikar Naftali; Fitria Handayani (GLOBAL HEALTH SCIENCE GROUP, 2024)
Cancer is a condition of abnormal cell growth, cells lose their normal control and mechanisms resulting in rapid and uncontrolled cell growth, as well as local tissue invasion and distant metastases. Quality of life is influenced by health status. A decrease in nutritional status often occurs as a result of cancer and its therapy. Due to the lack of food intake such as appetite, swallowing ability, absorption in the body and treatment therapy actions taken, coupled with chemotherapy. The aim of this study was to determine the effect of nutrition on the quality of life of cancer patients. Methods: Researchers used the scoping review method. The article search used databases from Sciencedirect, Scopus, and Pubmed with the research time January 2019 to December 2023, with the keywords influence